Infections Caused by Acinetobacter baumannii in Recipients of Hematopoietic Stem Cell Transplantation - Al-Anazi, Khalid Ahmed; Al-Jasser, Asma M. (Frontiers in Oncology, 2014)
Acinetobacter baumannii (A. baumannii) is a Gram-negative, strictly aerobic, non-fermentative coccobacillus which is widely distributed in nature. Recently, it has emerged as a major cause of health care-associated infections in addition to its capacity to cause community acquired infections. Risk factors for A. baumannii infections and bacteremia in recipients of hematopoietic stem cell transplantation include: severe underlying illness such as hematological malignancy, prolonged use of broad-spectrum antibiotics, invasive instrumentation such as central venous catheters or endotracheal intubation, colonization of respiratory, gastrointestinal or urinary tracts in addition to severe immunosuppression caused by using corticosteroids for treating graft versus host disease. The organism causes a wide spectrum of clinical manifestations, but serious complications such as bacteremia, septic shock, ventilator-associated pneumonia, extensive soft tissue necrosis and rapidly progressive systemic infections that ultimately lead to multiorgan failure and death are prone to occur in severely immunocompromised hosts. The organism is usually resistant to many antimicrobials including penicillins, cephalosporins, trimethoprim-sulfamethoxazole, almost all flouroquinolones and most of the aminoglycosides. The recently increasing resistance to carbapenems, colistin and polymyxins is alarming. Additionally, there are geographic variations in the resistance patterns and several globally and regionally resistant strains have already been described. Successful management of A.baumannii infections depends upon appropriate utilization of antibiotics and strict application of preventive and infection control measures. In uncomplicated infections, the use of a single active beta-lactam may be justified, while definitive treatment of complicated infections in critically ill individuals may require drug combinations such as colistin and rifampicin or colistin and carbapenem.